National Geographic investigates ancient Egypt archaeology unlocks the secrets of Egypt's past - Rubalcaba, Jill.; National Geographic Society (U.S.) (Washington, DC : National Geographic, 2007)
Learn about the discoveries that are bringing Egypt's history to light today.
1. Yesterday Comes Alive - 2. Letters in Clay - 3. The Tomb of King Tut - 4. The Tomb Builders - 5. The Pyramid Builders - 6. A New Discovery - 7. Saving the Temples.
OSLIS\Gale Nat Geo eBooks(2/2/23).
Includes bibliographical references (p. 60) and index.
Description based on print version record.
Keywords: Egypt -- Antiquities -- Juvenile literature; Excavations (Archaeology) -- Egypt -- Juvenile literature; Egypt -- History -- Juvenile literature; Egypt -- Antiquities; Excavations (Archaeology) -- Egypt; Egypt -- History; Electronic books- OSLIS; Electronic books